2013
DOI: 10.1007/s11356-013-1924-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and sources of antibiotics and their metabolites in river water, WWTPs, and swine wastewater in Jiulongjiang River basin, south China

Abstract: In this study, the occurrence and sources of five cataloged antibiotics and metabolites were studied in Jiulongjiang River basin, south China. Nineteen antibiotics and 13 metabolites were detected in water samples from 16 river sampling sites, wastewater from 5 swine-raising facilities, and effluent from 5 wastewater treatment plants (WWTPs). The results showed that 12 antibiotics and 6 metabolites were detected in river water samples. Sulfonamides (SAs) and their metabolites were detected at high concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…China; Yin et al, 2013 ; Mao et al, 2015 ). Other factors such as a rapid degradation (including environmentally relevant conditions; Soeborg et al, 2004 ; Sanderson et al, 2005 ; Zhang et al, 2013 ; Li et al, 2016 ), formation of metabolites (even at a higher concentration than the parent molecule; Halling-Sorensen et al, 2002 ; Kolpin et al, 2002 ; Bonvin et al, 2013 ; Jiang et al, 2013 ), and distribution (into sediments rather than the water column; Li et al, 2012 ; Liang et al, 2013 ; Chen and Zhou, 2014 ; Xu et al, 2014 ) may have resulted in these antibiotics being below the detection limit. On the other hand, it is known that low concentrations of antibiotics or their metabolites have been associated with selectivity for antibiotic resistant bacteria ( Gullberg et al, 2011 ; Sandegren, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…China; Yin et al, 2013 ; Mao et al, 2015 ). Other factors such as a rapid degradation (including environmentally relevant conditions; Soeborg et al, 2004 ; Sanderson et al, 2005 ; Zhang et al, 2013 ; Li et al, 2016 ), formation of metabolites (even at a higher concentration than the parent molecule; Halling-Sorensen et al, 2002 ; Kolpin et al, 2002 ; Bonvin et al, 2013 ; Jiang et al, 2013 ), and distribution (into sediments rather than the water column; Li et al, 2012 ; Liang et al, 2013 ; Chen and Zhou, 2014 ; Xu et al, 2014 ) may have resulted in these antibiotics being below the detection limit. On the other hand, it is known that low concentrations of antibiotics or their metabolites have been associated with selectivity for antibiotic resistant bacteria ( Gullberg et al, 2011 ; Sandegren, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The two prongs enter a typical subtropical macro-tide estuary (ES) on the southwest coast of Taiwan Strait. Previous studies have reported the contamination of nutrients and antibiotics in the JLR [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…The lowest concentration of OFL (25.1 ng/L) in water samples from the rivers in the present study was higher than that in tributaries of the Seine in France (maximum, 18 ng/L), 35 and the median concentration of OFL (110 ng/L) in water samples from the rivers was comparable to that in the Pearl River (108 ng/L) 36 but higher than that in the Jiulong river basin (46 ng/ L). 37 To our best knowledge, PIPE was detected for the first time at a median concentration of 7.2 ng/L and a frequency of 53.3%. It should be noted that GATI, a fourth-generation quinolone, was detected in all 45 samples from the rivers at a relatively high concentration (1.6−116.4 ng/L; median, 16.5 ng/L).…”
Section: ■ Results and Discussionmentioning
confidence: 72%